Web-Based New Student Registration Information System Using the Codeigniter Framework at Tk Islam Maulana Siddiq, Serang City - Mansyuri, Umar; Gunadi, Slamet; Aryono, Gagah Dwiki Putra; Arief, Rahadian; Hawariz, Mamdu Mahsan (Indonesian Research Journal on Education, 2024)
The rapid development of technology that affects everything from various life activites is used as a guide to solving existing problems. The above technological developments facilitate daily activities in various fields such as education, potics, social, and others. Competition in the world of education has created intense competition between schools with one another. The problem in this study is that the web-based registration of prospective new students at maulana siddiq Islamic kindergarten is still done manually which results in inefficient use of time, place, cost and manpower. There needs to be a system that can manage registration more effectively by using a website-based information system. With the school website playing an important role in the process of inputting data. This study uses the waterfall method in designing a new student registration system, where the design begins with analysis, design, coding and testing. The web-based developed system uses the CodeIgniter Framework with the PHP (Hypertext Preprocessor) programming language and MySQL as the database. The stages of website testing using black box testing before the system is used show that the website is running according to its functionality. The results of the developed website are able to assist in managing new student registration data and can make reports directly so that becomes effective and efficient.